Comparing the Health Care Experiences of Medicare Beneficiaries with and without Depressive Symptoms in Medicare Managed Care versus Fee‐for‐Service. (14th September 2015) - Martino, Steven C.; Elliott, Marc N.; Haviland, Amelia M.; Saliba, Debra; Burkhart, Q.; Kanouse, David E.
Abstract : Objective: To compare patient experiences and disparities for older adults with depressive symptoms in managed care (Medicare Advantage [MA]) versus Medicare Fee‐for‐Service (FFS). Data Sources: Data came from the 2010 Medicare CAHPS survey, to which 220, 040 MA and 135, 874 FFS enrollees aged 65 and older responded. Study Design: Multivariate linear regression was used to test whether case‐mix‐adjusted associations between depressive symptoms and patient experience differed for beneficiaries in MA versus FFS. Dependent measures included four measures of beneficiaries' experiences with doctors (e.g., reports of doctor communication) and seven measures of beneficiaries' experiences with plans (e.g., customer service). Principal Findings: Beneficiaries with depressive symptoms reported worse experiences than those without depressive symptoms regardless of coverage type. For measures assessing interactions with the plan (but not for measures assessing interactions with doctors), the disadvantage for beneficiaries with versus without depressive symptoms was larger in MA than in FFS. Conclusions: Disparities in care experienced by older Medicare beneficiaries with depressive symptoms tend to be more negative in managed care than in FFS. Efforts are needed to identify and address the barriers these beneficiaries encounter to help them better traverse the managed care environment.